A compound produced by Helicoverpa armigera male genitalia activates a conserved pheromone receptor - Dongdong Sun; Yutong Zhang; Song Cao; Xiaoqing Wang; Qian Cao; Sai Zhang; Yang Liu (Journal of Integrative Agriculture, 2025)
Mating behavior is essential for sexual reproduction, and it is often modulated by key chemical cues. In many moth species, males find compatible mates through the reception of sex pheromones which are released by females. Pheromone receptors (PRs) are key elements in sensing these chemical signals. Concurrently, male moths emit a complex blend of volatile compounds during courtship; however, the mechanisms for recognizing putative male pheromones remain poorly understood. Here, we employed gas chromatography coupled with electroantennographic detection and mass spectrometry to analyze the volatile compounds produced by males of the cotton bollworm, Helicoverpa armigera. Three candidate male sex pheromones were identified, with (Z)-7-dodecen-1-yl acetate (Z7-12:OAc) eliciting the most pronounced electrophysiological response in the male antenna. The olfactory receptor neuron (ORN) ORN-a in Type A trichoid sensilla was shown to respond to Z7-12:OAc by conducting single sensillum recording (SSR) assays. Additionally, we found that the OR13s from five Heliothinae species responded to Z7-12:OAc by using the Xenopus oocyte expression system and two-electrode voltage-clamp recording. Our findings identified a candidate for evaluation in future behavioral studies of the poorly understood chemosensory recognition mechanisms underlying male sex pheromones. If its relevance is supported by behavioral data, this knowledge may facilitate the design of novel olfactory regulators for effective pest control strategies involving mating disruption.